2018
DOI: 10.3390/toxins10070298
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Barrier Function in Chronic Kidney Disease

Abstract: The kidneys are key contributors to body homeostasis, by virtue of controlled excretion of excessive fluid, electrolytes, and toxic waste products. The syndrome of uremia equals the altered physiology due to irreversible loss of kidney function that is left uncorrected for, despite therapeutic intervention(s). The intestines and its microbial content are prime contributors to this syndrome. The intestinal barrier separates the self (or the so-called “milieu intérior”) from the environment. In the large intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 65 publications
0
56
0
3
Order By: Relevance
“…Among them, Faecalibacterium and Roseburia produce SCFA and are reduced in ESKD patients, consistent with SCFA insufficiency that is observed in gut dysbiosis [ 49 , 50 , 51 , 52 ]. Of note, we did not assess other factors affecting the blood level of indoxyl sulfate, most notably the function of the gut-blood barrier, which has been reported to be disturbed in CKD subjects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Faecalibacterium and Roseburia produce SCFA and are reduced in ESKD patients, consistent with SCFA insufficiency that is observed in gut dysbiosis [ 49 , 50 , 51 , 52 ]. Of note, we did not assess other factors affecting the blood level of indoxyl sulfate, most notably the function of the gut-blood barrier, which has been reported to be disturbed in CKD subjects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have shown that intestinal barrier defects have been associated with a wide array of diseases, including both enteral disorders such as irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD) ( Brandtzaeg, 2011 ; Michael et al., 2012 ; Salim and Söderholm, 2015 ), and extra-intestinal disorders such as nonalcoholic fatty liver disease, pancreatitis, and obesity ( Luca et al., 2009 ; Yan et al., 2012 ; Xiong et al., 2018 ). The latest study found that intestinal barrier function decreased in CKD as well ( Alice et al., 2015 ; Briskey et al., 2016 ; Meijers et al., 2018 ). Since the glomerular filtration rate is dramatically reduced in CKD ( Wong et al., 2014 ), the heavy influx of urea from body fluids to the gastrointestinal tract, was firstly hydrolyzed to ammonia and then converted to ammonium hydroxide (NH4OH), leading to increased intestinal pH.…”
Section: Discussionmentioning
confidence: 99%
“…59 Increased intestinal permeability on barrier compromise also results in movement of pathogen-associated molecular patterns (PAMPs) into the blood, 1 which activate the innate immune response. Release of PAMPS has consequences for organs, including brain and kidney, 10,60 but also for liver. 1 The liver and gut are linked through the portal circulation.…”
Section: Disruptions In Intestinal Barrier Function and Liver Diseasementioning
confidence: 99%